Train teachers in digital citizenship to facilitate a sustainable education system - Piceci, Luigi; Mariani, Anna Maria; Peluso Cassese, Francesco (Form@re - Open Journal per la formazione in rete, 2021)
The technological development of the last twenty years, starting in Europe from the increased availability of Internet resources to the concept of the digital citizen, has involved our society at all levels, affecting politics, businesses, families and all forms of education and teaching at each and every level. The COVID pandemic that began in 2020 has led to further acceleration, so much so that both the Digital Agenda for information technology in public administration 2020-2022 (AGID) and the Action Plan for Digital Education 2021-2027 focus on a strong digital component in everyday life. A psychoeducational protocol for digital skills in teachers is hereby provided, tested on a sample over the course of 8 weeks. In order to be able to assess initial and final competences, a questionnaire on digital competences has been developed and validated, based on DigComp 2.1. Formare gli insegnanti alla cittadinanza digitale per facilitare un sistema educativo sostenibile. Lo sviluppo tecnologico degli ultimi vent’anni, a partire in Europa dalla maggiore disponibilità di risorse Internet fino al concetto di cittadino digitale, ha coinvolto la nostra società a tutti i livelli, interessando la politica, le imprese, le famiglie e tutte le forme di istruzione e didattica ad ogni livello. La pandemia di COVID iniziata nel 2020 ha portato a un’ulteriore accelerazione, tanto che sia l’Agenda Digitale per le tecnologie dell’informazione nella pubblica amministrazione 2020-2022 (AGID) sia il Piano d’Azione per l’Educazione Digitale 2021-2027 si concentrano su una forte componente digitale nella vita di tutti i giorni. Viene fornito un protocollo psicoeducativo per le competenze digitali degli insegnanti, testato su un campione nel corso di 8 settimane. Per valutare le competenze iniziali e finali è stato sviluppato e validato un questionario sulle competenze digitali, basato su DigComp 2.1.